PERAN SISTEM INFORMASI MANAJEMEN (SIM) DALAM PENGAMBILAN KEPUTUSAN TERHADAP MANAJEMEN BISNIS - Akhmad, Sevia Diah Pratiwi; Muhammad irwan fadli Nasution; Muhammad irwan fadli Nasution; Suci Sundari (JEBS (Journal of Economic and Business Student), 2023)
The Information is an important part and must be filled in immediately. Information about a company or organization is important, especially when deciding to solve a problem. If the organization does not have the right information, then the organization will not function properly. Without an information system, the company does not know how far the development of the company and its business has advanced and cannot make accurate decisions because there is no available information or facts to make new strategies within the organization or within the company. that they are no worse than the competition. The research used a descriptive qualitative method, in which the researcher collected various sources of information through a literature review and literature study. Then the researcher presents the information obtained with several stages of writing, namely description, reduction and selection. The results obtained are based on the research method Management information system (MIS) is a survey process that involves looking at data in a predetermined or special way. The management information system must provide both avenues. The information system itself must also review all data and submit requests for overall checks. At the design stage, matters related to SIM providing a decision model will be processed against existing data to obtain decision results or alternative solutions.